Stakeholder Analysis in Libyan Construction Industry - Hraisha, Ahmed A. Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Scholars in the construction management field have highlighted the importance of analyzing and managing the project stakeholders effectively, since the project success or failure is related to their perceptions of the value created by the project, and the nature of their relationship with the project team. This study intended to facilitate the analysis of the construction industry stakeholders by providing an original framework model. This framework displays a clear process for stakeholders’ identification, prioritization, and classification. And its results provide the basic information needed to engage and manage the stakeholders efficiently in the construction projects. In order to apply this framework in Libyan construction industry (LCI), a questionnaire survey has been conducted by using an internet questionnaire forums and also by distributing printed copies. The survey has targeted the Libyan academic researches and industry professionals for their reviews. The application of the framework in LCI and the analysis of the survey responses have resulted an identification of twenty one stakeholders involved in Libyan construction projects in addition to their roles, objectives and impact in the projects, and a prioritization of these stakeholders based on the salience of their attributes towards the project. Furthermore, based on these results, a classification of the identified parties has made by positioning them in stakeholder assessment matrix. Keywords: Stakeholder Analysis, Stakeholder Identification, Prioritisation, Stakeholder Salience, Salience Assessment Matrix, Libya Construction Industry,Framework Model.

ÖZ: İnşaat yönetimi alanındaki akademisyenler, proje paydaşlarını etkili bir biçimde analiz etme ve yönetmenin önemini vurgulamaktadırlar çünkü projenin başarılı olup olmaması; onların projenin yarattığı değer hakkındaki algılarına ve proje ekibiyle olan ilişkilerine bağlıdır. Bu çalışma, inşaat endüstrisinin paydaşlarının analizini, orijinal bir çerçeve model geliştirerek kolaylaştırmayı amaçlamaktadır. Bu çerçeve, paydaşlar için çok açık bir süreci ortaya koymaktadır: Tanımlama, önceliklendirme ve sınıflandırma. Sonuçlar, paydaşların etkili bir şekilde inşaat projelerine dahil olması ve bu projeleri yönetmesi için ihtiyaç duyulan temel bilgiyi sağlamaktadır. Libya inşaat endüstrisindeki (LİE) bu çerçeveyi uygulamak için, internet anket forumları kullanılarak ve basılı kopyalar dağıtılarak bir araştırma anketi oluşturulmuştur. Araştırmaya, Libyalı araştırmacı akademisyenler ve endüstride çalışan profesyoneller görüşleri alınmak üzere dahil edilmiştir. LİE’ndeki bu çerçevenin uygulaması ve araştırma cevaplarının analizi, Libya inşaat projelerine dahil olan yirmi bir paydaşın tanımı ve buna ek olarak, rolleri, amaçları, projelerdeki etkileri ve projeye olan katkıları doğrultusunda paydaşların önceliklendirilmesine ilişkin bir sonuç ortaya çıkarmıştır. Ayrıca, bu sonuçlara dayanarak tanımlanan taraflar paydaş değerlendirme matriksine koyularak onların bir sınıflandırması yapılmıştır. Anahtar Kelimeler: Paydaş analizi, Paydaş Tanımlama, Önceliklendirme, Paydaş Belirginliği, Pelirginlik Değerlendirme Matriksi, Libya Inşaat Endüstrisi, Çerçeve Model.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assoc. Prof. Dr. İbrahim Yitmen.
Keywords: Civil Engineering; Project management - Process control; Stakeholder Analysis; Stakeholder Identification; Prioritisation; Stakeholder Salience; Libya Construction Industry; Framework Model; Salience Assessment Matrix